The Relationship Between Writing Motivation and Writing Self Efficacy in Students Who Become Writers: Hubungan Antara Motivasi Menulis dengan Writing Self Efficacy pada Mahasiswa yang Menjadi Penulis - Puspita, Lintang Dyah; Iriani, Ririn Dewanti Dian Samudra (Psikologia : Jurnal Psikologi, 2022)
This study is a study of the relationship between writing motivation and writing self efficacy in students who are writers at the University of Muhmmadiyah Sidoarjo. With the aim of knowing the relationship between writing motivation as the independent variable and writing self efficacy as the dependent variable. This type of reaserch is correlational quantitative. Subjects in this study using a sample of 96 students who become writers, taken using saturated sampling technique. The data collection technique was carried out using two psychological scale with a Likert model, namely a writing motivation scale with writing self efficacy scale. The hypotesis in this study is that there is a positive relationship between writing motivation and writing self efficacy for student who become writers at University of Muhammadiyah Sidoarjo. Using the Pearson Produck Moment Correlation analysis technique with the help of SPSS 20 For Windows. The results of the correlation coefficient in this study were 0,615 with a significance of 0,000 so that it was stated that there was a relationship between writing otivatin and writing self efficacy for student who were writers at the Universitiy of Muhammadiyah Sidoarjo, in other words the initial hypotesis in this study was accapted. The effective contribution between writing motivation and writing self efficacy in this tudy amounted to 37,9%.